The Performance of a Revised Simplified Arakawa–Schubert (SAS) Convection Scheme in the Medium-Range Forecasts of the Korean Integrated Model (KIM) - Han, Ji-Young; Hong, Song-You; Kwon, Young Cheol (Weather and forecasting, 2020)
The Korea Institute of Atmospheric Prediction Systems (KIAPS) has developed a new global numerical weather prediction model, named the Korean Integrated Model (KIM). This paper presents the cumulus parameterization scheme (CPS) used in KIM, which originates from the simplified Arakawa–Schubert (SAS) convection scheme in the National Centers for Environmental Prediction (NCEP) Global Forecast System (GFS) and has undergone numerous modifications in an effort to improve the medium-range forecast skill for precipitation and large-scale fields. The modifications include the following: 1) the threshold of the trigger condition is updated to consider the dependency on the environmental relative humidity (RH) averaged over the subcloud layer in order to suppress the trigger of convection in dry low-level environments; 2) the entrainment rate is modified to increase the sensitivity to environmental humidity, so that enhanced entrainment under lower RH conditions leads to a greater decrease in the strength of the convection that develops in drier environments; 3) the autoconversion parameter from cloud condensate to convective precipitation is changed to have a temperature dependency above the freezing level; 4) the closure is modified to consider rapidly varying boundary layer forcing; 5) the effect of the convection-induced pressure gradient force in convective momentum transport is enhanced in the upper part of the convective updrafts; and 6) scale awareness that enables a mass-flux CPS to work seamlessly at various grid sizes across gray-zone resolutions is addressed. The evaluation of medium-range forecasts with the KIM CPS reveals higher forecast skill, especially over the tropics, in comparison with its original version.